Akzeptanz psilocybin-assistierter Therapie in den deutschsprachigen Ländern - Hartter, Nina; Däumichen, Marvin; Schmidt, Christopher; Wolff, Max; Gründer, Gerhard; Jungaberle, Henrik (Der Nervenarzt, 2025)
Background Clinical studies with psilocybin in combination with psychotherapy show promising results for the treatment of various mental disorders; however, there still exists a lack of knowledge, rejection and prejudice towards this new form of therapy among doctors, psychotherapists and patients. The aim of this study was to gain a representative impression, as far as possible, of the level of information and attitudes towards the implementation of psilocybin-assisted therapy (PAT) among mental health experts, patients and the general population. Methods An online survey was used to collect information on the attitudes and knowledge of 1456 participants and to test the effect of a brief intervention. Results were determined using analyses of variance and regression models. Results Regression analyses showed that a higher knowledge score and self-assessed level of knowledge, own treatment experience and also own experience with psychedelics predicted more positive attitudes towards the introduction of PAT, F(8, 1447)= 154.646, p< 0.001, R2= 0.39. Providing information about the potential of PAT only led to higher acceptance when combined with information about its risks. Conclusion The results indicate that participants are optimistic about the implementation of PAT. The relationship between knowledge and acceptance was confirmed. The fact that receiving balanced information leads to higher acceptance should be taken into account when educating and reporting on PAT.